Produção contínua de ésteres etílicos a partir do óleo de soja utilizando etanol supercrítico em leito estruturado - Andrade, Simone Belorte de (2012)
This study aimed to investigate the production of ethyl esters of soybean ou by transesterification in supercriticai conditions. in order to achieve our goal, we evaluated the process variables (temperature, pressure, molar ratio of ou ethanol and reaction time) and the effect of the presence of water in reaction regarded to yield esters for reactions conducted in structured bed reactor with giass beads. The effect of temperature in the range of 250-325 °C, pressure of 100-200 bar, the molar ratio of oil ethanol 110 to 1 40, the reaction time of 21- 52 minutes and the addition of 5 and 10% mass of water to alcohol used in the reaction mixture were evaluated The new configuration of the bed structured reactor with glass beads proved to be a favorable one for the production of ethil esters. The proposed configuration resulted in an improvement in a transfer between stages of the reaction mixture which provided the conversion of esters The results show that increasing the temperature, pressure, the molar ratio of oil: ethanol, reaction time and adding water to the reaction, also promote the conversion of esters. The highest yield found (90.46%) was provided 325 r °C, 200 bar, 1:40 molar ratio of oil: ethanol, 10% water and 52 minutes of reaction.